Design and experimental testing of a gas cluster ion accelerator - 曾晓梅 Vasiliy Pelenovich 刘传胜 付德君 (Chinese physics C, 2017)
A gas cluster ion beam（GCIB） system with cluster energy up to 12 keV has been designed. To facilitate pumping of the nozzle chamber and increased pressure of the gas source up to 10 atm, pulse mode was used for the gas feeding. Argon was employed as the working gas. To separate monomers from clusters, both electromagnet and retarding electrode were utilized. A maximal pulsed cluster current of 90 nA has been achieved. The shape of pulsed ion beam currents has been analyzed in detail at different applied magnetic and retarding electric fields.